The multi-target small-molecule inhibitor SB747651A shows in vitro and in vivo anticancer efficacy in glioblastomas - Arnon Møldrup Knudsen (Nature Portfolio, 2021)
Abstract Glioblastoma multiforme is the most common primary brain tumor and among the most lethal types of cancer. Several mono-target small molecule-inhibitors have been investigated as novel therapeutics, thus far with poor success. In this study we investigated the anticancer effects of SB747651A, a multi-target small-molecule inhibitor, in three well characterized patient-derived glioblastoma spheroid cultures and a murine orthotopic xenograft model. Concentrations of 5–10 µM SB747651A reduced cell proliferation, spheroid formation, migration and chemoresistance, while apoptotic cell death increased. Investigation of oncogenic kinase signaling showed decreased phosphorylation levels of mTOR, CREB, GSK3 and GYS1 leading to altered glycogen metabolism and formation of intracellular reactive oxygen species. Expression levels of cancer stemness marker SOX2 were reduced in treated tumor cells and SB747651A treatment significantly prolonged survival of mice with intracranial glioblastoma xenografts, while no adverse effects were observed in vivo at doses of 25 mg/kg administered 5 days/week for 8 weeks. These findings suggest that SB747651A has anticancer effects in glioblastoma. The cancer-related pathophysiological mechanisms targeted by SB747651A are shared among many types of cancer; however, an in-depth clarification of the mechanisms of action in cancer cells is important before further potential application of SB747651A as an anticancer agent can be considered.